At the Botanic Gardens, Trinidad - (:unkn) unknown (Davidson and Todd, Ltd., Trinidad, 2009)
A path lined with tropical trees and plants in the Botanical Gardens that leads to the Governor General's Residence which is situated on the grounds of the gardens.
Colour: Sepia; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Botanical gardens--Trinidad and Tobago; Trees--Trinidad and Tobago; Plants--Trinidad and Tobago; Public buildings--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Historic buildings--Trinidad and Tobago; Governors--Dwellings--Trinidad and Tobago; President's House, The (Trinidad and Tobago)